KEMATANGAN GONAD UDANG GALAH Macrobrachium rosenbergii DENGAN PAKAN ALAMI YANG BERBEDA - Ayu Safitri; Suci Puspita Sari; Ardiansyah Kurniawan (Jurusan Akuakultur, Universitas Bangka Belitung, 2019)
The reduction of dependency on the consumption of giant prawns (Macrobrachium rosenbergii) from river catchments has essential significance for its natural sustainability. Artificial prawn reproduction gives benefits to the economy and the environment. Applicable maturation technology is needed to facilitate community participation in cultivating giant prawns. The increasing level of gonad maturity (TKG) in this study uses different natural feed in the form of golden snails, earthworms, and squid. Observation of giant prawn maturity was carried out using macroscopic morphological characteristics on the dorsal cephalothorax. All treatments were able to increase TKG from level 2 to level 3 for 30 days of treatment with golden snail intake, giving the fastest increase (7.33 ± 1.1 days) and followed by squid (11.3 ± 2 days) and earthworms (17.67 ± 2 days). Growth of giant prawns with golden snail, earthworm, and squid feed is 1.2, -4.33, -0.83 for weights and 1.03, 0.4, and 0.53 for length. The three natural foods can be utilized for the maturation of giant prawn gonads, but it is necessary to add a source of carbohydrates as energy intake.